1985
DOI: 10.1037/0012-1649.21.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Development of social-moral reasoning among Kibbutz adolescents: A longitudinal cross-cultural study.

Abstract: The development of social-moral judgment among Israeli kibbutz adolescents was studied from the perspective of Kohlberg's theory of moral judgment development. The sample included 92 adolescents, 64 of whom were interviewed longitudinally over a two-to-nine year period. The study's purpose was to evaluate the validity of Kohlberg's model and measure in a cross-cultural context and to assess the cultural uniqueness of social-moral reasoning among kibbutzniks. The developmental findings strongly supported the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 15 publications
0
47
0
2
Order By: Relevance
“…Findings from a variety of studies support the hierarchical and sequential nature of Kohlberg's stages (e.g., see Colby & Kohlberg, 1984;Colby et al, 1983;Edwards, 1985;Rest, 1979;Snarey, Reimer, & Kohlberg, 1985a;Turiel, 1973; Walker, deVries, & Bichard, 1984;Walker & Taylor, 1991). For example, results of a 20-year longitudinal study of Kohlberg's moral stage development reported by Colby et al (1983) indicated that subjects appeared to use a consistent logic or form of reasoning across a variety of moral dilemmas.…”
Section: Empirical Support For Hierarchical and Sequential Nature Of mentioning
confidence: 86%
See 1 more Smart Citation
“…Findings from a variety of studies support the hierarchical and sequential nature of Kohlberg's stages (e.g., see Colby & Kohlberg, 1984;Colby et al, 1983;Edwards, 1985;Rest, 1979;Snarey, Reimer, & Kohlberg, 1985a;Turiel, 1973; Walker, deVries, & Bichard, 1984;Walker & Taylor, 1991). For example, results of a 20-year longitudinal study of Kohlberg's moral stage development reported by Colby et al (1983) indicated that subjects appeared to use a consistent logic or form of reasoning across a variety of moral dilemmas.…”
Section: Empirical Support For Hierarchical and Sequential Nature Of mentioning
confidence: 86%
“…In particular, Gilligan (1977Gilligan ( ,1982 has argued that Kohlberg's moral stages have a built-in bias against females because they emphasize the acceptance of justice over the more traditional female values of caring and responsibility. However, Kohlberg's scoring system has been revised in recent years to avoid this problem (Hoffman, Paris, & Hall, 1994) and there is little evidence of sex differences in moral development (e.g., Colby, et al, 1983;Lapsley, 1996;Rest, 1979Rest, , 1993Silberman & Snarey, 1993;Snarey, Reimer, & Kohlberg, 1985a;Vasudev, 1988;Walker, 1984Walker, , 1989Walker, deVries, & Trevethan, 1987). Walker (1984), conducted one of the more thorough reviews of the literature and found that sex differences in moral reasoning are exceedingly rare.…”
Section: Sex Differences In Moral Developmentmentioning
confidence: 99%
“…It has been used in over 1,000 research studies, with "hundreds of thousands" of subjects from the late 1970s to the present and it has been used in 40 countries, with new studies taking place at the rate of approximately 150 per year [28]. A majority of moral reasoning theorists support that the construct of moral reasoning and stages of moral reasoning are cross-cultural as evidenced by the broad international use of the Defining Issues Test [43].…”
Section: Instrumentmentioning
confidence: 99%
“…É considerada uma teoria universalista. Assim sendo, acreditava que os seres humanos poderiam chegar a uma plena consciência moral, autônoma e independente da cultura do país ou do grupo social ao qual a pessoa pertencesse [14][15][16][17] . O autor argumentou que o desenvolvimento moral ocorreria em seis estágios, nos quais cada um teria suas próprias características e estaria na dependência da idade das pessoas.…”
unclassified
“…Ademais, pelos mesmos motivos não se poderia transpor um estágio antes do outro 12,15 . Adolescência, autonomia e pesquisa em seres humanos Carol Gilligan 6 , ao estudar mais especificamente a psicologia do desenvolvimento da mulher, analisou e descreveu a formação da identidade feminina e a evolução do seu juízo moral, desde a adolescência até a idade adulta.…”
unclassified